2021
DOI: 10.20450/mjcce.2021.2127
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermodynamic parameters on alkaline activator of geopolymers and structure of geopolymers

Abstract: In this research, the starting precursor material is metakaolin, which was obtained by calcining domestic kaolinite clay. Thermodynamic parameters: densities, viscosities, speed of sound and refractive index of four series of alkaline activatorswere determined over the temperature range from 15 to 60oC of process of geopolymerization. The samples were characterized by X-ray diffraction (XRD), FTIR and Raman Spectroscopy, Scanning Electron Microscopy (SEM), and Energy-Dispersive X-Ray (EDX) Spectroscopy. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In previous work by Ivanovic et al [ 30 ], velocity of sound values shows a small increase with increasing temperature for solutions with lower NaOH concentration, which may be an indicator of increased ion mobility in solution. Since the changes during heating of the alkaline activator are in the range of 15–60 °C below 2.0% when it comes to density and refractive index, and since the velocity of sounds is slightly above 3.0%, this indicates the thermodynamic stability of the activator leading to dissolution of the initial aluminosilicate types and creation of a new Na–aluminosilicate gel structure of geopolymer samples.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In previous work by Ivanovic et al [ 30 ], velocity of sound values shows a small increase with increasing temperature for solutions with lower NaOH concentration, which may be an indicator of increased ion mobility in solution. Since the changes during heating of the alkaline activator are in the range of 15–60 °C below 2.0% when it comes to density and refractive index, and since the velocity of sounds is slightly above 3.0%, this indicates the thermodynamic stability of the activator leading to dissolution of the initial aluminosilicate types and creation of a new Na–aluminosilicate gel structure of geopolymer samples.…”
Section: Resultsmentioning
confidence: 77%
“…Ivanovic et al examined the thermodynamic parameters (viscosity, density, refractive index, velocity of sound) of the alkaline activator and examined the influence on the synthesis of geopolymers [ 30 ]. It was confirmed that, with the knowledge of thermodynamic parameters, there is a better understanding of the first phase of gel formation of geopolymer structure.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics for all the samples are the vibration bands with a maximum of ~3450 cm −1 and bands at 1635 cm −1 , which are attributed to stretching vibrations and the deformation of physically adsorbed water molecules (H-O-H) on the surface. The presented spectra in Figure 5 of all samples show a strong peak at approximately 1000 cm −1 , which is associated with the Si-O-Si asymmetric stretching vibration and fingerprints of polymerization [ 26 ]. In the part of the spectrum corresponding to wave numbers at 1000–1200 cm −1 , there are two broad bands: the Si-O-Si stretching vibration and the Si-O and Si (Al)-O stretching vibration.…”
Section: Resultsmentioning
confidence: 99%
“…The vibrational band with a maximum at approximately 1050 cm −1 is assigned to Si-O stretching of tetrahedra, in which Si is surrounded by three oxygen bridges and one non-bonding oxygen. The structure Si-O-X (X = Al, Si), the building blocks of geopolymers, and the shift of vibrational bands corresponding to the Si-O-X bond stretching toward the lower wavenumbers indicate the lengthening of the O-X bond of this structure and the reduction in the bond angle [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geopolymer manufacture is one of the effective methods for creating a rapidly inorganic ionic conductor [25]. Furthermore, the thermodynamic properties of the mixture alkali activator (density, viscosity, speed of sound) are conducive to easier arrangement of engineering processes [26]. Afterwards, geopolymers have a number of advantages: heat and acid/alkaline resistance, immense strength, and beneficial solidification of toxic waste [27].…”
Section: Introductionmentioning
confidence: 99%